Implementation of Decision Tree Algorithm for Student Interest Analysis Based on Subjects at MTs Aisyiyah Binjai - Haekal, Muhammad; Irvan, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
Education plays a vital role in improving the quality of human resources, where students’ interest in learning subjects is one of the key factors influencing academic achievement. However, not all students show the same level of interest in every subject, which affects their motivation and performance. This study aims to analyze students’ subject preferences at MTs Aisyiyah Binjai using the Decision Tree algorithm. The method was chosen for its ability to process complex academic data, discover hidden patterns, and identify influential factors in determining students’ interests. The results are implemented into a web-based system that allows schools to flexibly monitor and evaluate students’ learning interests. This research is expected to assist schools in developing more effective learning strategies, enhancing students’ motivation, and supporting better academic achievement.